Podemos: ¿regeneración democrática o impugnación del orden? Transición, frontera política y democracia - Javier Franzé (Cahiers de Civilisation Espagnole Contemporaine)
Spanish politics has been shaken by the emergence of Podemos. This paper poses the question of whether Podemos represents a democratic regeneration or a refutation of order. It analyzes their discourse in relation to the narrative of the Transition, which legitimizes the Spanish political order, taking the 15M discourse as a historical precedent. While the Transition conceptualized democracy as consensus and avoidance of fratricide, the 15M discourse disassociates Transition and democracy by evaluating the existing order as an oligarchy to democratize. Podemos, in the wake of 15M, was organizing to fight for political power and, in a first stage, was directly confronting the Transition discourse. "The Caste" and the "Regime of '78" impeded democracy, thereby requiring a constitutional process. In a second stage, Podemos disassociates "the caste" from the institutionality of '78 and proposes to "throw out the caste" in order to restore democracy. The demand for constitutional process vanishes, and along with it, the political boundary drawn in the first stage, thus depoliticizing democracy as neutral rules of the game.